Socio-Cultural Determinants of Food Choice Among Iranian Students at Universiti Putra Malaysia - Namakyan, Ashraf (2010)
There are more than 5000 Iranian students in Malaysia and this number is increasing according to local authorities. Iranian students in Malaysia face the problem of food choice as Malaysian and Iranian food cultures are totally different. Due to the cultural differences, they are not so keen to adopt local food pattern and local food ingredients. The high price of Iranian foods in Malaysia discourages the practice of Iranian food when dining out. The unavailability of some Iranian food ingredients also restricts the students’ option for preparing Iranian foods. Thus, the socio-cultural factors are important determinants of the students’ food choice which can cause a tendency to unhealthy food habits and consumption of low nutrient dense foods like fast foods and snacks. The objectives of this study are to explore major food problems among Iranian students at Universiti Putra Malaysia, and to compare the food intake and food pattern of the students before and while staying in Malaysia. To determine socio-demographic and cultural factors affecting the food choice of the students in Malaysia is another main objective of the study. The research design includes an explorative study through focus groups followed by a self-administered questionnaire assessing socio-demographic factors, food frequency questionnaire and acculturation. Iranian students, who had stayed in Malaysia for more than three months, were recruited through convenient sampling. A total of 308 subjects participated in the study, of which 164 were male (53.2%) and 144 (46.8%) were female. Results showed a significant increase in skipping main meals, consumption of fast foods and snacks and a significant decrease in the consumption of vegetable, dairy products and seafood among Iranian students in Malaysia in comparison to while living in Iran (P<0.05). These changes also showed some correlation to socio-economical situation of Iranian students in Malaysia. Positive attitude towards Malaysian foods and consumption of Malaysian foods were affected by acculturation and length of stay in Malaysia. On the other hand, consumption of Malaysian foods, acculturation and length of stay in Malaysia had negative relationship with the consumption of fast foods. Furthermore, acculturation, length of stay in Malaysia and the positive attitude towards Malaysian foods are significant predictive factors in the food choice of the students. The study suggests that subjects need to get accustomed to local food ingredients and actively receive information about local food resources to be able to gain a healthier diet.